(untitled) (Journal of the College of Basic Education, 2022)
Examinations have become a regulating force that directs the work of both the teacher and the student. So I gained Examinations and evaluation methods are of great importance in the educational field. If the exams get worse, then the education gets worse. If reformed, this would be a means to reform its curriculum, just as the methods of examinations and evaluation have made great progress. at the present time. Evaluation became inseparable from the educational process, and it has a diagnostic and therapeutic function that helps to correct its course. At the present time, the calendar is characterized by comprehensiveness, objectivity, and diversity.